Establishment of herbaceous plants in heavy metal contaminated soils inoculated with arbuscular mycorrhizal fungi - Carneiro, Marco Aurélio Carbone; Siqueira, José Oswaldo; Moreira, Fátima Maria de Souza (Pesquisa Agropecuaria Brasileira, 2001)
The establishment of herbaceous plants in soil contaminated by heavy metals (HM) and inoculated with arbuscular mycorrhizal fungi (AMF) was evaluated in the present study. The experiment was conducted in trays, in a 5 x 2 factorial, being five proportions of contaminated soil with or without inoculation with arbuscular mycorrhizal fungi (AMF). Seeds of eight grass species and a mustard (Brassica sp.) were planted and allowed to grow for 120 days under greenhouse conditions and assessed through two cuts. In the first cut grass species were severely affected by soil contamination, whereas the mustard was little affected, thus exhibiting high tolerance. In the second cut, the effect of soil contamination was negligible for the grasses, and inoculation with AMF increased dry matter yield by 24% over non-inoculated controls. Inoculation also had positive effects on root dry matter and colonization. Shoot concentrations of Cd, Zn and Pb were higher in mustard in the first cut than in grasses in both cuts. Although inoculation had no effect on grass dry matter in the first cut, it enhanced accumulation of Zn, Cd and Pb in these plants in the second cut. Higher tolerance of mustard to heavy metals allowed its growth and enhanced Zn, Cd and Pb uptake from the contaminated soil. The extraction of these elements may have contributed for the enhanced subsequent development of the grasses and therefore facilitated plant establishment.